Beet Flour-Based Pancake Experiment - Destiana, Isna; Cornellia, Ayu Hellena; Santoso, Budi (Gastronary, 2024)
This study is an experimental research. The research method used in this study is qualitative. The research was conducted within the campus environment of STP AMPTA Yogyakarta. Four experts specializing in pastry were selected as the sources of information. The data collection method used in this research involves primary data obtained through observation and interviews. The testing method in this research includes organoleptic testing, and the data collected were analyzed using descriptive analysis. The results show that the fourth experiment conducted by the researcher yielded the most desirable outcome. Based on the organoleptic test results, beet flour pancakes showed a slight difference compared to wheat flour pancakes in terms of colour, with beet flour pancakes having a dark brown colour, while wheat flour pancakes had a light brown colour. In terms of taste, beet flour pancakes differed from wheat flour pancakes. The aroma of beet flour pancakes was fragrant but still had a beet scent. The texture of beet flour pancakes was not as smooth as that of wheat flour pancakes, as beet flour has a coarser texture. Overall, based on the colour, aroma, taste, and texture, beet flour can be considered as a potential base ingredient for making pancakes.